Legal Liability For Holders Of Electricity Supply Business Licenses Without Electrical Safety (A Study At Pln Nusantara Power Umro Medan Power Plant Maintenance Implementation Unit (UPHK) - Hasibuan, Erwin; Maswandi, Maswandi; Frensh, Wenggedes (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
This research, entitled "Legal Liability for Holders of Electricity Supply Business Licenses Without Electrical Safety (A Study at PLN Nusantara Power UMRO UPHK Medan)," aims to examine: (1) the regulations applied by PLN in granting business licenses to electricity support service providers; (2) PLN's procedures for issuing procurement permits; and (3) the legal accountability imposed on electricity support services within UMRO UPHK Medan. This study employs normative legal research, focusing on the analysis of legal norms as outlined in laws, regulations, and scholarly literature. These legal materials are examined and connected to the research problems to provide a clear understanding of the application of electrical safety obligations. The research is descriptive-analytical, presenting legal provisions and factual conditions while conducting an in-depth juridical analysis to describe the implementation of electrical safety and the consequences of non-compliance. The research prioritizes secondary data, including legal documents and literature, which are critically examined to uncover scientific truth through a systematic and consistent normative method. The research results are expected to provide a comprehensive overview of regulatory mechanisms, licensing procedures, and forms of legal liability for violations of electrical safety standards, as well as recommendations to strengthen supervision and law enforcement in Indonesia's electricity sector.